Screening vulnerability in the Anthropocene: Island of The Hungry Ghosts and the eco-ethics of refugee cinema - Chu, Kiu-Wai (2023)
Zygmunt Bauman points out that between 1950 and the early 2010s, the estimated number of displaced people, or ‘people in transition’, increased from one to 12 million, ‘but as many as 1 billion refugees-turned-exiles and ensconced in the nowhereland of camps are predicted for 2050’. ‘[Refugee] Camps ooze finality’, he writes, ‘not the finality of destination, though, but of the state of transition petrified into a state of permanence’. This global mass of exiles, refugees and asylum seekers is both confined within highly guarded detention centres (‘fencing in’), and at the same time excluded from the general public (‘fencing out’). In short, as Bauman puts it, ‘becoming an inmate of a refugee camp means eviction from the world shared by the rest of humanity’. In recent decades we have seen a growing number of film and media representations that address the conditions caused by the global refugee crisis. This essay begins with a short critique of social activist, artist and filmmaker Ai Weiwei’s ‘Refugee Series’ and proceeds to a study of Australian filmmaker Gabrielle Brady’s Island of the Hungry Ghosts (2018), a documentary set on the tiny Christmas Island, geographically situated in Southeast Asia. It explores the cinematic subjectivity of the displaced human and more-than-human beings in the Anthropocene epoch, and asks how, with such collective fatigue in the face of the global refugee situation, can we address these important issues and present them via cinematic means?